Faktor - Faktor Yang Mempengaruhi Performa Saham Pada Industri Pertambangan di Indonesia - Haki, Billy Adriyadi; Setiawan, Amelia; Djajadikerta, Hamfri (Politeknik Ganesha Medan, 2024)
This study is aimed to examine the effect of profitability, liquidity, firm size, board size, and net income on stock returns. The population that is used in this study is all of the mining companies listed on the Indonesian Stock Exchange within the 2017-2022 period, resulting in 62 companies. A purposive sampling method is used in this study, and by considering several criteria, a sample of 8 companies with an observation period of 5 years is chosen. This study uses multiple linear regression analysis using IBM SPSS 27. The study has shown that at a 95% significance level, it can not be concluded that liquidity, profitability, net income, and board size have partial effects on stock return. However, at the same significance level, it can be concluded that firm size have a partial effect on stock return. Simultaneously, at a 95% significance level, liquidity, profitability, net income, firm size, and board size have effect on stock returns. Profitability, liquidity, firm size, board size, and net income simultaneously have Adjusted R Square of 22.9%, which highlights the fact that there are other variables not included in this study that have effect on stock returns.